In vivo evaluation of a transdermal codrug of 6-β-naltrexol linked to hydroxybupropion in hairless guinea pigs - Kiptoo, Paul K. (2008)
6-β-Naltrexol is the major active metabolite of naltrexone, NTX, a potent μ-opioid receptor antagonist used in the treatment of alcohol dependence and opioid abuse. Compared to naloxone, NTX has a longer duration of action largely attributed to 6-β-naltrexol. This study was carried out in order to determine percutaneous absorption of a transdermal codrug of naltrexol, 6-β-naltrexol-hydroxybupropion codrug (CB-NTXOL-BUPOH), in hairless guinea pigs as well as to evaluate the safety of 6-β-naltrexol for development as a transdermal dosage form. This codrug may be useful in the simultaneous treatment of alcohol dependence and tobacco addiction. The carbonate codrug traversed the skin at a faster rate than 6-β-naltrexol. 6-β-naltrexol equivalent steady state plasma concentrations of 6.4 ng/ml were obtained after application of the codrug as compared to 1.2 ng/ml from 6-β-naltrexol base. The steady state plasma concentration of hydroxybupropion after codrug application was 6.9 ng/ml. Skin sensitization and irritation tested in the hairless guinea pigs using the Buehler method revealed that 6-β-naltrexol had no skin sensitizing potential. The method was validated with a known sensitizer, p-phenylenediamine, which induced sensitization in 90% of the animals. 6-β-Naltrexol caused only mild transient skin irritation after the initial application of the patch. During subsequent applications, erythema was slightly increased but no skin damage was observed. In conclusion, a transdermal codrug of 6-β-naltrexol could be a viable alternative treatment for alcohol and opiate abuse.